(3NRGfI GdCOH hdH dHGH dSGf GdYQHs - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s
(3ChdgG (B:s
(3fMeOc jG ef ThGgO BjGJg YfjI Yf GdTQM hGdHjGf s
(3BNQgG (B:s
(3TQM GdTGgO GdQGHY GdCQHYjf HYO GdeGFJjf hgh bhd CeQF GdbjS hdG SjeG jheG HOGQI LdLd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B41s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs